Factors associated with body image dissatisfaction in Portuguese adolescents: obesity, sports activity and TV watching - Coelho, Eduarda Maria Rocha Teles de Castro (2016)
This cross-sectional study intended to determine the prevalence of body image dissatisfaction and associated factors in Portuguese adolescents (N=529, 10-18 years, 53.7% male and 46.3% female). The prevalence of body dissatisfaction (estimated through Collins's silhouettes) was 58%. Multivariate logistic regression analyses showed that the variables associated were: obesity, watch TV over 2 hours/day and practice sport activities 4 or more days/week. In male, obesity and watch TV over 2 hours/day were related to body dissatisfaction and among female only obesity had statistical significance. It is necessary to considered different public health interventions for men and women in order to reduce this high body image dissatisfaction.